Solar-hydrogen production with reduced graphene oxide supported CdxZn1-xS photocatalysts - ÖZKAYA, ALİ RIZA; KOCA, ATIF; SARIOĞLU, CEVAT; KARACA ALBAYRAK, FATMA; UĞUZ NELİ, ÖZLEM (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Reduced graphene oxide (RGO)/CdxZn(1-x)S composites were firstly synthesized by thermal sulfurization method in one pot with elemental sulfur as sulfur source. By using one pot synthesis, CdxZn(1-x)S particles were decorated on the RGO sheets during sulfurization of Cd2+ and Zn2+ precursors. This synthesis method eased the control of the particle sizes of CdxZn(1-x)S by providing homogenous decoration of RGO with CdxZn(1-x)S particles and increased the strength between RGO sheet and CdxZn(1-x)S particles, which enhanced charge carrier mobility rate. Here, RGO in the composite structure supplied high electron conductivity, high adsorption capacity and extended light absorption ability. Thus, prepared RGO/CdxZn(1-x)S composites enhanced the photocatalytic activity. The crystal systems, lattice parameters, band gaps and surface morphologies of all photocatalysts are characterized to determine the factors that affected the photocatalytic activities of the composites. After that, the photocatalytic activities of prepared photocatalysts were tested by measuring H-2 evolution rates. Among the composites, RGO/Cd0.7Zn0.3S structure possessed the highest H-2 production rate (141.6 mu molh(-1)) and apparent quantum efficiency (19.4%). (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Graphene; Hydrogen production; Photocatalyst; Reduced graphene oxide (RGO); Solar energy; Sulfurization; IN-SITU SYNTHESIS; SOLID-SOLUTION; EFFICIENT; WATER; TEMPERATURE; GENERATION; EVOLUTION; NANOSTRUCTURES; NANOCOMPOSITES; NANOMATERIALS